Marginalized Population Scopes and Opportunities for Universal Health Coverage in Bangladesh (Bangladesh Medical Journal, 2025)
Achieving universal health coverage (UHC) is central to the health-for-all agenda and the Sustainable Development Goal (SDG) 3.8. Bangladesh has made significant progress in health outcomes, yet large segments of marginalized populations remain left behind. To review the current status of health provision and financing for marginalized populations in Bangladesh, identify major barriers and enablers, and highlight opportunities and policy options to accelerate progress toward UHC. Narrative review of published literature, policy papers, and programme reports (2010–2025) focusing on marginalized populations and UHC in Bangladesh, emphasizing service coverage, financial protection, and equity. Marginalized groups-defined by poverty, geography, ethnicity, gender, disability, or informal employment- face disproportionate barriers to essential services and financial protection. Out-of-pocket (OOP) health spending remains high (~11% of household budgets), pushing many families into poverty. Although the Government of Bangladesh has committed to achieving UHC by 2030, barriers such as under-financing, governance gaps, and inequitable access persist. Achieving UHC in Bangladesh requires an explicitly pro-equity approach targeting marginalized populations first. With sustained political commitment, innovative financing, and inclusive governance, Bangladesh can move closer to the SDG 3.8 target of leaving no one behind.Bangladesh Med J. 2024 Sept; 53(3): 36-39